Assessment of energy balance against the nutritional status of women carriers in the brickfields of West Bengal. Issue 3 (2nd July 2016) - Bandyopadhyay, Bijetri; Sen, Devashish
Abstract : The Indian brick industry is an unorganized sector in which large numbers of migrant women workers are employed. A survey was conducted on 62 women workers working in different brickfields of West Bengal to assess their physiological workload, nutritional profile, total energy expenditure and energy balance. Energy intake was calculated using physiological fuel values of carbohydrate, fat and protein. From the results it is seen that 13% of the sample population falls under severe (grade III) chronic energy deficiency. The average daily consumption of the workers was comparatively lower than their daily energy expenditure, considering the nature of the job which falls under heavy to extremely heavy categories. This negative energy balance is effectively observed in the nutritional anthropometry data. Thus, an immediate ergonomics intervention with better nutrition should be implemented to improve the health status of the workers so they can safely continue to work for a longer period.